So you want to write a novel - Stanek, Lou Willett Ph.D. (New York Avon Books, 1994)
Practical advice, hands-on help. Respected author and professional writing instructor Lou Willett Stanek's New York workshop have enabled scores of aspiring novelist to realize their dreams of completing credible and compelling manuscripts. Here, in a positive, "user-friendly" format, she offers not only encouragement and motivation, but clear step-by-step instructions to accomplish your goal--from original conception through final draft.

Learn how to:
-Set up and stick to a writing schedule
-Create unforgettable characters
-Follow strong plotting and solid structure guidelines
-Choose a viewpoint and develop conflict
-Handle flashbacks and transitions
A gift of Prof. Jovenal Velasco.
Keywords: Creative writing; Fiction -- Authorship